A study of migraine in systemic lupus erythematosus. Issue 1 (February 1982) - Isenberg, D A; Meyrick-Thomas, D; Snaith, M L; McKeran, R O; Royston, J P
Abstract : An increased prevalence of classical migraine was found in 30 female patients with systemic lupus erythematosus (SLE) compared with an age and sex-matched control group by means of a detailed questionnaire. No significant difference were found between the patients and controls, who had classical and common migraine or visual auras without headache, with regard to a family history of migraine, the age of onset of the migraine, Raynaud's phenomenon, or use of oral contraceptives. Increased activity of the lupus was not generally associated with an increase in migraine attacks. It is suggested that migrainous phenomena may be a feature of SLE.